Evaluation of the Physical Parameters on Ischemic Heart Disease Patients Using Echocardiography - Mohammed, Marrwa K.; Essa, Samar I. (Iraqi Journal of Science, 2022)
Background: Left ventricular function and volumes have major diagnostic and prognostic importance in patients with various cardiac diseases, such as ischemic heart disease which is a life-threatening heart disease condition characterized by systolic dysfunction and a decrease in cardiac output. According to left ventricular ejection fraction, the degree of ischemic heart disease was classified as mild, moderate, and severe. To determine cardiac function and hemodynamics, the echocardiography technique is used, which is a noninvasive diagnostic method.Patients and Methods: The study included 216 patients between 25 and 75 years old; 121 males and 95 females; 265 normal individuals (age range: 25 to 75 years old); 84 males and 181 females. Doppler echocardiography was used to assess left ventricular function. The measurements included left ventricular end-diastole diameter (LVIDd), left ventricular end-systole diameter (LVIDs), and left ventricular ejection fraction (LVEF%). Results show a significant correlation in the values of EDV, ESV and LVEF (all: p < 0.05). The change difference in left ventricular ejection fraction (LVEF) was (61.88%), (47.57%), and (36.76%), respectively, for all degrees of ischemia. While the change difference in left ventricular end diastolic volume (LVEDV)between patients and control groups was (173.38%), (248.83%), and (289.82%), respectively. On the other hand, the change in left ventricular end systolic volume (LVESV) was (258.73%), (495.13%), and (569.72%), respectively, for all degree of ischemia.Conclusion: The findings suggest that diastolic dysfunction is more common in patients than in healthy people. This could be due to the adverse effects of ischemic heart disease on the cardiac muscle. These changes in left ventricular structure may include left ventricular hypertrophy, increase in stiffness, and reduction in compliance.